The Polish accounting system and IFRS implementation process in the view of empirical research - Konrad Grabinski; Marcin Kedzior; Joanna Krasodomska (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The paper analyses the process of implementing International Financial Reporting Standards (IFRS) in Poland. It presents the development of accounting in its historical perspective focusing on such events as the partitions of Poland, wars, the period of the centrally planned economy, the period of the political and economic transformation and Poland's membership in the European Union. The authors discuss the relationships between tax and financial accounting and identify the main users of information generated by the accounting system; also, they describe the Polish capital market as well the organizations which contribute to the development of accounting. The further part of the work presents the scope of IFRS implementation, identifying four stages of the process as well as the entities which apply international standards. The paper stresses that Polish accounting regulations are based on the simultaneous implementation of IFRS convergence and adoption. The authors point to a number of benefits derived by companies from IFRS implementation including the higher quality of financial statements and their comparability, lower costs of capital as well. Also, the authors present an extensive review of literatures and the results of major empirical research in the area of IFRS implementation in Poland.
Keywords: M41; 650; IFRS; Poland; implementation process